"Flipped" clinical rotations: A novel approach. (6th August 2022) - Xiong, Wei; Singh, Simran; Wilson‐Delfosse, Amy; Jones, Robert; Nielsen, Craig; Chalkley, Carol; Logio, Lia
Abstract: Background: Near the beginning of the COVID‐19 pandemic in the United States, medical students were pulled out of all in‐person patient care activities. This resulted in massive disruption to the required clinical rotations (clerkships), necessitating creative curricular solutions to ensure continued education for medical students. Approach: In response to the lockout, our school adopted a "flipped" clinical rotations model that assigned students to remote learning activities prior to in‐person patient care activities. This approach allowed students to continue their clinical education virtually with a focus on knowledge for practice while awaiting return to the shortened in‐person portions of their rotation. In planning the modified clinical curriculum, educational leaders adhered to several guiding principles including ensuring flexible remote curricular components that would engage students in active learning, designating that no rotation would be completely virtual, and completing virtual educational activities and standardised exams before students returned to in‐person experiences. Evaluation: End of rotation evaluations and standardised exam scores were analysed to determine the effectiveness of this model. Despite the disruption associated with the pandemic and the rapid implementation of the "flipped" rotations, students continued to rate the overall experiences as highly as traditional clinical rotations. Students also performed similarly on standardised exams when compared to cohorts from other classes at the same experience level. Implications: While borne out of necessity during a pandemic, the lessons learned from our implementation of a "flipped" rotations model can be applied to address problems of capacity and clinical preparedness in the clinical setting.